Studies on the Relationship Between Xanthine Oxidase and Histamine Release During Intestinal Ischemia-Reperfusion - Boros Mihály; Kaszaki József; Bakó László; Nagy Sándor (1992)
Recent studies have demonstrated a connection between xanthine oxidase-generated reactive oxygen intermediates and histamine release during ischemia-reperfusion. In the present work, the effect of modulation of the endogenous histamine level on the xanthine oxidase activity was examined during the reperfusion of a canine ileal segment following a 2 hr of complete ischemia. The xanthine oxidase activity and the plasma histamine level peaked simultaneously at the beginning of reperfusion, reaching mean values of 14.9 nmol/ml/min and 12.1 nmol/l, respectively. Pretreatment with aminoguanidine, a blocker of diamine oxidase (histaminase), resulted in significantly higher levels of histamine during reperfusion, but this elevation was not accompanied by a further increase in xanthine oxidase activity. Pretreatment with the mast cell stabilizer cromolyn significantly diminished the rise in plasma histamine level, with an unchanging activity of xanthine oxidase. No significant alteration could be observed in the postocclusive activity of xanthine oxidase following the intra-arterial administration of 0.5, 1, or 5 nmol of histamine during the last 10 min of the ischemic period. These data suggest that the amount of histamine liberated during reperfusion does not result in a further increase in the xanthine oxidase activity. The release of histamine is not a cause, but rather an effect of the elevated activity of intestinal xanthine oxidase.
Keywords: Klinikai orvostan